2020
DOI: 10.1002/aoc.5466
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid promoted dehydration of amides to nitriles catalyzed by [PSiP]‐pincer iron hydrides

Abstract: The dehydration of primary amides to their corresponding nitriles using four [PSiP]‐pincer hydrido iron complexes 1–4 [(2‐Ph2PC6H4)2MeSiFe(H)(PMe3)2 (1), (2‐Ph2PC6H4)2HSiFe(H)(PMe3)2 (2), (2‐(iPr)2PC6H4)2HSiFe(H)(PMe3)2 (3) and (2‐(iPr)2PC6H4)2MeSiFe(H)(PMe3)2 (4)] as catalysts in the presence of (EtO)3SiH as dehydrating reagent was explored in the good to excellent yields. It was proved for the first time that Lewis acid could significantly promote this catalytic system under milder reaction conditions than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…The 1 H NMR spectrum of 6a showed a singlet in the high-field region at −17.7 ppm assignable to Fe–H, two sets of signals corresponding to the inequivalent Mes groups, and four multiplets assignable to the pyridyl ligand, in addition to a singlet of the Cp* ligand. The signal corresponding to the hydride on the iron center was shifted to a higher magnetic field relative to those of Cp*­(OC)­(L)­FeH (L = CO and PMe 3 , −11 to −15 ppm), Cp*­(OC)­Fe­(SiR 3 ) 2 H (−11 to −14 ppm), , and Cp*Fe­(η 2 -H-ER 3 ) (E = Si and Ge, −12 to −14 ppm) and was comparable to that reported for Fe­(diphosphine)­(PR 3 ) 2 (SiR 3 )H (−14 to −19 ppm). , The IR spectrum showed one intense absorption band at 1918 cm –1 assignable to νCO. The absorption band was comparable to that of Cp*­(OC)­Fe­(LB)­(η 1 -aryl) (1903–1913 cm –1 , LB: Lewis base) …”
Section: Results and Discussionmentioning
confidence: 77%
“…The 1 H NMR spectrum of 6a showed a singlet in the high-field region at −17.7 ppm assignable to Fe–H, two sets of signals corresponding to the inequivalent Mes groups, and four multiplets assignable to the pyridyl ligand, in addition to a singlet of the Cp* ligand. The signal corresponding to the hydride on the iron center was shifted to a higher magnetic field relative to those of Cp*­(OC)­(L)­FeH (L = CO and PMe 3 , −11 to −15 ppm), Cp*­(OC)­Fe­(SiR 3 ) 2 H (−11 to −14 ppm), , and Cp*Fe­(η 2 -H-ER 3 ) (E = Si and Ge, −12 to −14 ppm) and was comparable to that reported for Fe­(diphosphine)­(PR 3 ) 2 (SiR 3 )H (−14 to −19 ppm). , The IR spectrum showed one intense absorption band at 1918 cm –1 assignable to νCO. The absorption band was comparable to that of Cp*­(OC)­Fe­(LB)­(η 1 -aryl) (1903–1913 cm –1 , LB: Lewis base) …”
Section: Results and Discussionmentioning
confidence: 77%
“…表 2 芳香族酰胺脱水制备腈的4种催化体系 范围为67%~92%. 随后, Li等 [169] 发现在PSiP配位的甲 硅烷基氢化铁络合物催化体系中, 添加Lewis酸可以有 效地促进催化活性, 降低反应温度, 反应条件更温和.…”
Section: 脱氢氧化生成腈unclassified
“…Figure26 Fe or Co complexes catalyzed dehydration of primary amides to nitriles with (EtO) 3 SiH[167][168][169][170] (color online).…”
mentioning
confidence: 99%
“…This is similar to hydrido iron(II) catalyst. 17 Recently, we reported that the classical [PSiP]-pincer iron hydride (2-Ph 2 PC 6 H 4 ) 2 -MeSiFe(H)(PMe 3 ) 2 was an efficient catalyst to dehydration of primary amides with the assistance of Lewis acid at 40 °C for 40 h. 18 On the basis of the above research, we attempt to design novel [PSiP] pincer ligands to synthesize [PSiP] pincer iron hydrids, even iron nitrogen complexes, and to explore the catalytic activity of these complexes for dehydration of primary amides. Recently, we reported that the N-heterocyclic σ-silyl [PSiP] pincer ligand 1 could stabilize iron hydride 2 (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is similar to hydrido iron­(II) catalyst . Recently, we reported that the classical [PSiP]-pincer iron hydride (2-Ph 2 P C 6 H 4 ) 2 ­Me Si Fe­(H)­(PMe 3 ) 2 was an efficient catalyst to dehydration of primary amides with the assistance of Lewis acid at 40 °C for 40 h …”
Section: Introductionmentioning
confidence: 99%